Fabrication of High-quality Periodic Ge Nanostructures via Water-based MAC Etching and Their Application for Photovoltaics - 윤여준 (The Graduate School, Ajou University, 2022)
Abstract Nano-patterned designs with well-defined morphologies, typically fabricated by dry etching, provide structural and optical advantages, inducing potential availability beyond limits of material. However, these structures, formed by high energy ion, can induce critical damage to the semiconductor surface and crystal structure, resulting in limitation of additional growth for device application. Recently, metal-assisted chemical (MAC) etching, wet based etching technique, has been attracted as a promising candidate for semiconductor patterning due to its merits such as process simplicity, low fabrication cost and anisotropic nanostructures with high aspect ratio. Moreover, this also produces a smooth surface without incurring ion induced surface damages. Even though there have been various advantages of MAC etching technology, germanium (Ge) approaches, which have reported as one of the superior material, have not been investigated with clear understanding since most of the reported study used randomly distributed catalysts. Furthermore, most of the experimental reports used strong acid solution, which breaks the lattice of the Ge surface, and therefore, MAC etching reaction as well as optimized solution composition for only Ge should be investigated for structural design with maintaining crystal quality. The primary goal of this dissertation is to understand Ge MAC etching reaction and design high-quality nanostructures suitable for epitaxial growth. In order to achieve the purpose, this research has been focused on three parts: water based Ge MAC etching reaction, design and optimization of periodic Ge nanostructures via Ge MAC etching technology, and photovoltaic application of periodic Ge nanostructures. First, Ge MAC etching reaction via water solution is investigated to realize Ge surface with high crystal quality. The inverse etching characteristic with periodic catalyst pattern is experimentally confimed in our results of MAC etching on Ge. The inverse etching reaction consecutively evolved during the MAC etching of Ge is discussed with experimental results and supporting literature. The reactions of electronic holes according to material characteristic and the location of etching have been systematically explained by the sequential change of metal-assisted chemical etching on Ge. As a result, the position of MAC etching reaction has to do with the movement of electrical holes, contributing to oxidation of semiconductors, and therefore, Ge, having the high mobility and diffusion coefficient of holes, indicate higher possibility of hole diffusion outside of the Catalyst−Ge interface, resulting in IMAC etching reaction. Second, the periodic Ge NP arrays have been fabricated on Ge (100) substrates by using SLP and water based IMAC etching technology. The charge and mass transport conditions are investigated to optimize nanoscale structural design for Ge surface quality. With optimized charge and mass transport mechanism, 2-inch wafer scale ordered periodic Ge NP arrays with smooth surface are successfully demonstrated on the first. Furthermore, the high-quality of Ge NP arrays are demonstrated from structural and optical analysis. Based on this result, the high-quality Ge NP arrays can be applied for epitaxial growth of optoelectronic device. Finally, the epitaxial structures of Ge solar cells are successfully grown on Ge substrates with NP arrays. Based on previous research, selective patterning process and MOCVD growth conditions are used to realize the Ge solar cell structure with NP arrays. Despite the different growth conditions between InGaP and Ge, heterogeneous material, no structural defects are observed at the interface between Ge NP arrays and InGaP. The Ge NP solar cells show a lower reflectance, and higher JSC and VOC compared to those of a planar cell. As a result, the PCE has been improved from 3.37% to 4.23% under 1 sun AM 1.5G conditions in the Ge NP solar cell with 500 nm diameter, and 200 nm height (under fixed period 1 μm). It has been demonstrated that Ge NP solar cells can have improved light absorption properties thanks to the light trapping effect and effective carrier collection. Throughout this dissertation, research results can provide deep insight for structural design of Ge nano and micro structures via metal-assisted chemical etching and the high-quality periodic Ge nanostructures can be expected to be very useful approach for various devices with additional material growth.
학위논문(박사)--아주대학교 일반대학원 :전자공학과,2022. 2
Keywords: Metal-assisted chemical etching; epitaxial growth; germanium; high-quality; inverse metal-assisted chemical etching; metalorganic vapor chemical vapor deposition (MOCVD); periodic nanostructure; photovoltaics; power conversion efficiency